Social Justice Innovation in Africa - Viljam Engström; Maija Mustaniemi-Laakso; Laura Stark (Routledge, 2024)
Adopting a multidisciplinary approach, this book discusses the potential of social innovation in the pursuit of social justice in Africa. In the twenty-first century, social innovation and entrepreneurship have attracted renewed attention as a way of promoting social justice and addressing challenges of poverty and inequality. Drawing on perspectives from human rights, economics, business, development studies and anthropology, this book illustrates the entangled relationship between societal areas and activities, as well as different actors (individuals, communities, business actors, non-governmental organisations and public authorities) in social innovation. It identifies various models of social innovation, ranging from grassroots initiatives to public policymaking, and discusses their impact on socioeconomic welfare. It analyses a broad range of original research data and incorporates localised understandings of social innovation, highlighting both the empowering potential of social innovation and the possibility that it could sustain or create inequalities. As such, this book deepens an understanding of what makes social innovation 'social' and 'just'. Arguing that social justice innovation can only be understood in context, this book will be of interest for researchers and policy makers across the fields of human rights, economics, business, development studies, anthropology and African studies.
Keywords: 300; Social Innovation; Social Justice; Entrepreneurship; Human Rights; Development Studies; Grass-Roots Initiatives; Socio-Economic Welfare; Anthropology